Thomas Buckingham : a critical edition with commentary of the first question of the Questiones super Sententias - Lee, AR (1975)
Rather more information is currently available about the life and works of Thomas of Buckingham than there was only a few decades ago, when L'Abbé A,.de Poorter, describing a manuscript containing Buckingham's Questiones super Sententias, was limited to saying: "Buckingham is the author of the second piece: the questions reproduced in folios 45 to 79 belong to his Commentary on the Sentences of which there exists one specimen at Florence (Laurenz.) and another at Paris (Bibl. Nat.). We owe this information to the kindness of R.P. Pelster, S.J., who promises us more ample information about Buckingham.” That it is now possible to write a reasonably full biography - albeit one subject to certain limitations - is due to the considerable work of Michalski, Chenu, Emden, Pantin, Robson and Weisheipl, among others. They have brought to light a body of materials for his life which may be regarded as exhaustive, at least insofar as all likely - and many unlikely - sources of information have been consulted. Some of these items have been published, but the majority are known only in brief references. Since, in common with most of his mediaeval contemporaries, Thomas of Buckingham has left the modern biographer a fragmentary corpus of materials from which to reconstruct his life, it is the nature of the materials themselves which justifies further attempts at reconstruction. As Robson has said of the materials for the life of Wyclif: "...the certain and authoritative sources for these years are so few and so stark that they permit, and even encourage, an assessment de novo." What is true of Wyclif, who has not lacked biographers, is at least equally true of Buckingham, for whose life the sources are even more limited and no less ambiguous, but who has received far less critical attention. But, if it is the fragmentary nature of the materials which prompts this enterprise, it follows that interpretation must be both careful and open; i.e. that a balanced assessment of the conclusions and inferences which may be drawn from the primary materials must be presented, with clear distinctions drawn between the information actually given and the conjectural links. Continued in thesis ...